IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KAWASAN WISATA TERPADU GUNUNG PADANG - Edgar Ferdrianda, Nabeel; Yusran, Rahmadani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The purpose of this study is to describe and evaluate the policy's implementation for the development of Gunung Padang's Integrated Tourism Area, as well as to pinpoint the elements that facilitate and impede its execution. The study was motivated by the issuance of Padang Mayor's Decree No. 100 of 2021, which established Gunung Padang as a leading tourist attraction. Van Meter and Van Horn's (1975) implementation model, which comprises six variables—policy standards and objectives, resources, attributes of implementing agencies, communication among organizations, economic-social-political conditions, and the disposition of implementers. Interviews, observation, and documentation were used to gather data. The findings demonstrate that the policy's implementation has been rather successful, bolstered by community involvement, legal certainty, and government commitment. There are still issues, though, like poor interagency collaboration, insufficient facilities, and a lack of human resources.